INVITACIÓN AL GEOTURISMO. REFLEXIONES SOBRE GEODIVERSIDAD Y POTENCIAL GEOTURÍSTICO EN LA PATAGONIA ARGENTINA - María de la Paloma Martínez Fernandez (Boletín Geográfico)
Geotourism as a type of nature tourism comes to fill an empty field on the use of geological resources of the landscape in Argentina. With an approach sustained by the ideas and progresses achieved along the last decades about sustainable tourism, geosites and geoparks are getting a boost worldwide. However, in Argentina this concept has not being incorporated yet within public or private touristic policies, despite owning a valuable geodiversity both scientific or aesthetically. Based on a review of concepts and foreign experiences on the subject, this article analyses the possibilities and parameters for geotourism developing in Argentinean Patagonia.